Relationship between Deciduous Molar Hypomineralization (HSMD) and Molar-Incisor Hypomineralization(HMI): A cross-sectional study (Research, Society and Development, 2023)
Considering that the development of deciduous second molars and first permanent molars and incisors begins at approximately the same time, the presence of hypomineralization in deciduous second molars (HSMD) should serve as a warning for the involvement of first permanent molars by molar-incisor hypomineralization (MIH). The aim of this study was to assess the prevalence of HSMD and MIH in children, and the association between both. A cross-sectional study was carried out with children treated at the Pediatric Dentistry Clinic at Ceuma University, in São Luís, Maranhão. The HMI was evaluated according to the criteria of the European Association of Pediatric Dentistry (EAPD) (presence/absence and degree of severity: mild and severe). The same HSMD evaluation criteria were adopted. Descriptive statistical analysis (frequency of HSMD and HMI; mean number of teeth injured by HSMD and HMI; severity of lesions: mild or severe), bivariate (comparison between sexes and age regarding the frequency of HSMD and HMI and the association between HSMD and hypomineralization of the first permanent molar - HPMP) and antibodies (Spearman) were performed, at a significance level of 5%. Forty children were examined, 25 males and 24 females. The prevalence of HSMD was 38.8% and MIH was 46.9%. As for the severity of injuries, the severe degree was more frequent for both HSMD and HMI (10/20.4% and 12/24.5%, respectively). There was a positive change between the factor under study (HSMD) and HPMP (r=0.513; p=0.001). Based on the findings, it was concluded that HSMD is related to MIH, which demonstrates the importance of professional monitoring of teeth likely to be involved by the defect from the moment of eruption in the oral cavity.